Chemical Constituents from n-Butanol Extract of Rabdosia japonica var. glaucocalyx - Xiang, Zhao-Bao; Liu, Xing-Yu; Heng, Lin-Sen; Chen, Yi-Wen (Asian Journal of Chemistry, 2014)
The n-butanol fraction of the dried whole plants of Rabdosia japonica var. glaucocalyx was isolated and purified by means of chromatography. Six compounds were obtained and their structures were identified by spectral analysis as glaucocalyxin G (1), arjunglucoside (2), kaempferol-3-O-rutinoside (3), quercetin-3-O-a-L-rhamnoside (4), rutin (5) and acacetin-7-O-b-D-glucoside (6). Compound 1 was a new ent-kaurane diterpenoid glycoside, compounds 2 and 3 have not been reported before from the plant source.